The Role Of Adiponectin, TNF-α And Glutathione In The Pathogenesis And Evolution Of Type 1 Diabetes - Szabo, Csilla Enikő (Diabetes Metab Syndr Obes, 2019)
INTRODUCTION: Type 1 diabetes (T1DM) is a chronic autoimmune or idiopathic condition, featuring complex and unique interactions between proteins and enzyme systems. The purpose of the present study is to investigate the role of AdipoQ +276G>T, TNF-α-308G>A, GSTT1/GSTM1 polymorphic variants in the development of T1DM. MATERIALS AND METHODS: The study is designed as a cross-sectional study, involving 72 diabetic cases and 90 controls. Genotyping was carried out according to specific protocols for the above-mentioned polymorphic variants. RESULTS: The G allele of AdipoQ was associated with the development of type 1 diabetes (OR 0.577, CI95% 0.336–0.802, p=0.001), similar to the GG and GA genotypes (OR 0.405, CI95% 0.156–0.654, p=0.001 and OR 0.623, CI95% 0.401–0.855, p=0.004). The G allele of TNF-α was marginally associated with the development of type 1 diabetes (OR 0.789, CI95% 0.579–0.956, p=0.005). The presence of the T1 genotype was a strong predictor for type 1 diabetes (OR 3.4, CI95% 1.433–6.243, p<0.001). CONCLUSION: The results of our study suggest that G alleles of AdipoQ and TNFα act as a protective factor in T1DM, while the T1 allele for GST could be considered a risk factor for the development of Type 1 diabetes in our study group.